A STUDY IN THE INFLUENCE OF SOCIAL MEDIA ON COMMUNICATIVE BEHAVIOR IN ALL WALKS OF LIFE - Ming Yang; Ali Salman (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
As technology and big data algorithms advance, more social media emerge and grow popular, attracting many individuals. Almost everyone relies on social media platforms like Weibo, WeChat, TikTok, and others for communication and socializing, but young people rarely realize how much their communication habits have changed. In our daily lives, communication is vital, and the means of communication are constantly linked to results, therefore they should be given more attention. Some difficulties caused by this new communication have been found. Thus, fixing them appears crucial. This study aims To investigate the improvement of communicative behavior using social media. By exploring how social media change the way of communication from different angles, this research aims to provide valuable insights for educators, mental health professionals, and policymakers seeking to distinguish the advantage and disadvantage brought by social media among people and raise some possible solutions to make full use of this type of platform. The result showed the effective communication, social interaction, and conflict management are the main aspects of communication behavior improvement using social media. This research contributes to both industry and academia by updating theoretical knowledge of the how the use of social media can improve the communication effectiveness to All Walks of Life in social science studies.